Socioeconomic inequality in the risk of intentional injuries among adolescents: a cross-sectional analysis of 89 countries - Probst, Charlotte; Kilian, Carolin; Rehm, Jürgen; Carvalho, Andre F.; Koyanagi, Ai; Lange, Shannon (Injury prevention, 2021)
Introduction In 2015, the elimination of hunger worldwide by 2030 was declared by the United Nations as a Sustainable Development Goal. However, food insecurity remains pervasive, contributing to socioeconomic health inequalities. The overall objective was to investigate the relationship between food insecurity and intentional injuries among adolescents. - Methods Individual-level data from the Global School-based Student Health Survey from 89 countries were used (370 719 adolescents, aged 12-17 years). Multilevel logistic regressions were used to examine the sex-specific association between the level of food insecurity (none, medium and high) and intentional injuries (interpersonal violence and suicide attempts), accounting for the clustering of observations within surveys. Random-effects meta-analyses were used to analyse dose-response relationships. - Results Medium and high food insecurity were associated with increased odds of reporting an injury from interpersonal violence among both sexes. A positive dose-response relationship was found, where each level increase in food insecurity was associated with a 30% increase in the odds of an injury due to interpersonal violence among boys (1.30; 95% CI 1.26 to 1.34) and a 50% increase among girls (1.53; 95% CI 1.46-1.62). The odds for suicide attempts increased by 30% for both sexes with each level increase in food insecurity (boys: 1.29; 95% CI 1.25-1.32; girls: 1.29; 95% CI 1.25-1.32). - Discussion The findings indicate that socioeconomic inequalities exist in the risk of intentional injuries among adolescents. Although additional studies are needed to establish causality, the present study suggests that the amelioration of food insecurity could have implications beyond the prevention of its direct consequences.
Published Online First 7 October 2020
Gesehen am 06.10.2021